2012
DOI: 10.1111/j.1757-5672.2012.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil for the Treatment of Lower Urinary Tract Symptoms in Japanese Men with Benign Prostatic Hyperplasia: Results from a 12‐week Placebo‐controlled Dose‐finding Study with a 42‐week Open‐label Extension

Abstract: Tadalafil (5.0 mg) had a favorable benefit-to-risk profile, supporting further investigation of tadalafil (5.0 mg) in Japanese men with BPH-LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
80
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(109 citation statements)
references
References 22 publications
27
80
1
1
Order By: Relevance
“…12,13 Results from three pivotal studies of Japanese, Korean, and/or Taiwanese men with BPH/LUTS showed that tadalafil 5 mg once-daily improved LUTS while offering a favorable safety profile compared with alpha-blockers or 5-alpha reductase inhibitor. [14][15][16] The results from these three Asian studies were also comparable with pivotal clinical studies of tadalafil in American and European men with BPH/LUTS. [17][18][19][20][21][22] The incidence/severity of BPH/LUTS has been shown to increase with increasing age; additionally, LUTS patients experience varying degrees of symptom severity, have comorbid conditions, or have prior exposure to BPH treatments, all of which might impact the efficacy of new therapies.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…12,13 Results from three pivotal studies of Japanese, Korean, and/or Taiwanese men with BPH/LUTS showed that tadalafil 5 mg once-daily improved LUTS while offering a favorable safety profile compared with alpha-blockers or 5-alpha reductase inhibitor. [14][15][16] The results from these three Asian studies were also comparable with pivotal clinical studies of tadalafil in American and European men with BPH/LUTS. [17][18][19][20][21][22] The incidence/severity of BPH/LUTS has been shown to increase with increasing age; additionally, LUTS patients experience varying degrees of symptom severity, have comorbid conditions, or have prior exposure to BPH treatments, all of which might impact the efficacy of new therapies.…”
supporting
confidence: 71%
“…[14][15][16] These studies were similar in design, participation criteria, and efficacy/safety measures. Individual study designs and results were previously published.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations